Novel FH mutations in families with hereditary leiomyomatosis and renal cell cancer (HLRCC) and patients with isolated type 2 papillary renal cell carcinoma. Issue 4 (12th March 2011) - Gardie, Betty; Remenieras, Audrey; Kattygnarath, Darouna; Bombled, Johny; Lefèvre, Sandrine; Perrier-Trudova, Victoria; Rustin, Pierre; Barrois, Michel; Slama, Abdelhamid; Avril, Marie-Françoise; Bessis, Didier; Caron, Olivier; et al.
Abstract : Background: Hereditary leiomyomatosis and renal cell cancer (HLRCC) is an autosomal dominant disorder predisposing humans to cutaneous and uterine leiomyomas; in 20% of affected families, type 2 papillary renal cell cancers (PRCCII) also occur with aggressive course and poor prognosis. HLRCC results from heterozygous germline mutations in the tumour suppressor fumarate hydratase ( FH ) gene. Methods: As part of the French National Cancer Institute (INCa) 'Inherited predispositions to kidney cancer' network, sequence analysis and a functional study of FH were preformed in 56 families with clinically proven or suspected HLRCC and in 23 patients with isolated PRCCII (5 familial and 18 sporadic). Results: The study identified 32 different germline FH mutations (15 missense, 6 frameshifts, 4 nonsense, 1 deletion/insertion, 5 splice site, and 1 complete deletion) in 40/56 (71.4%) families with proven or suspected HLRCC and in 4/23 (17.4%) probands with PRCCII alone, including 2 sporadic cases. 21 of these were novel and all were demonstrated as deleterious by significant reduction of FH enzymatic activity. In addition, 5 asymptomatic parents in 3 families were confirmed as carrying disease-causing mutations. Conclusions: This study identified and characterised 21 novel FH mutations and demonstrated that PRCCII can be the only one manifestation of HLRCC. Due to the incomplete penetrance of HLRCC, the authors propose to extend the FH mutation analysis to every patient with PRCCII occurring before 40 years of age or when renal tumour harbours characteristic histologic features, in order to discover previously ignored HLRCC affected families.